Impact of biofertilisers on iron homeostasis and grain quality in the rice variety Uma under Elevated CO2 - Bhavya, M. S. P.; Manju, R. V.; Viji, M. M.; Roy, S.; Anith, K. N.; Beena, R. (Frontiers in Plant Science, 2023)
The diminishing nutritional quality of rice with increasing concentration of atmospheric CO2 is currently a major global concern. The present experiment was designed with an objective to assess the impact of biofertilizers on grain quality and iron homeostasis in rice under elevated CO2 conditions. A Completely randomized design with four treatments [(KAU, POP (control), POP+Azolla, POP+PGPR, POP+AMF)], each replicated thrice under ambient and elevated CO2 conditions was followed. The analyzed data revealed that the yield, grain quality, iron uptake and its translocation were found to be modified in an unfavorable manner under elevated CO2, which reflected in the lower quality and iron content of the grains. The response of iron homeostasis in the experimental plants to the application of biofertilizers, especially plant growth promoting rhizobacteria (PGPR), under elevated CO2 strongly suggests the possibility of utilizing them for designing iron management strategies to achieve higher quality in rice.